Genome-wide identification of heterotrimeric G protein genes in castor (Ricinus communis L.) and expression patterns under salt stress - Mubo Fan; Jiayu Li; Tongjie Zhang; Hongyan Huo; Shiyou Lü; Zhibiao He; Xiaoyu Wang; Jixing Zhang (BMC Genomics)
Abstract Background Heterotrimeric G proteins are crucial signaling molecules involved in cell signaling, plant development, and stress response. However, the genome-wide identification and analysis of G proteins in castor (Ricinus communis L.) have not been researched. Results In this study, RcG-protein genes were identified using a sequence alignment method and analyzed by bioinformatics and expression analysis in response to salt stress. The results showed that a total of 9 G-protein family members were identified in the castor genome, which were classified into three subgroups, with the majority of RcG-proteins showing homology to soybean G-protein members. The promoter regions of all RcG-protein genes contained antioxidant response elements and ABA-responsive elements. Go enrichment analysis displayed that RcG-protein genes were involved in the G protein-coupled receptor signaling pathway, regulation of root development, and response to the bacterium. Real-time PCR showed varying responses of all RcG-protein genes to salt stress. RcGB1 was notably expressed in both roots and leaves under salt treatment, suggesting that it may be an essential gene associated with salt tolerance in the castor. Conclusions This study offers a theoretical framework for exploring G-protein function and presents potential genetic assets for improving crop resilience through genetic enhancement.